1993
DOI: 10.1007/bf00271371
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of postoperative swelling and pain by dexamethasone after operative removal of impacted third molar teeth

Abstract: In a placebo-controlled double-blind study, we examined the effect of perioperative oral administration of 6 mg dexamethasone, given once 12 h before and once 12 h after osteotomy of two impacted molar teeth, on postoperative edema, limitation of jaw opening, and intensity of postoperative pain. On the first day after surgery the difference in the increase in cheek swelling was 54.3% (P < 0.001) as measured with a tape, 46% (P < 0.001) measured with a gauge in the first molar area and 29% (P < or = 0.056) by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 17 publications
0
49
0
Order By: Relevance
“…3 Thoracic epidural analgesia with morphine-bupivacaine combination improves analgesia in the first 24 hr following laparoscopic cholecystectomy. 4 Preoperative administration of dexamethasone by oral 5,6 and iv 7,8 routes has been shown to reduce overall pain scores and analgesic requirements in the postoperative period without any apparent adverse effect. Wang et al 9 showed that epidural administration of dexamethasone reduces the incidence and severity of …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Thoracic epidural analgesia with morphine-bupivacaine combination improves analgesia in the first 24 hr following laparoscopic cholecystectomy. 4 Preoperative administration of dexamethasone by oral 5,6 and iv 7,8 routes has been shown to reduce overall pain scores and analgesic requirements in the postoperative period without any apparent adverse effect. Wang et al 9 showed that epidural administration of dexamethasone reduces the incidence and severity of …”
Section: Discussionmentioning
confidence: 99%
“…3 Thoracic epidural analgesia with morphine-bupivacaine combination improves pain relief during the first 24 hr following laparoscopic cholecystectomy. 4 Preoperative administration of dexamethasone has been reported to reduce postoperative pain through both oral 5,6 and iv 7,8 routes of administration. While epidural steroids are effective in the treatment of low back pain, 9 their potential postoperative analgesic benefits have not been evaluated.…”
Section: B Enefits Of Laparoscopic Cholecystectomymentioning
confidence: 99%
“…Coxibs were of similar efficacy to nsNSAIDs in acute postoperative dental pain (Chen et Perioperative steroid administration reduced swelling and trismus but not pain, following third molar extraction (Markiewicz et al, 2008 Level I) and reduced postoperative nausea (Baxendale et al, 1993 Level II; Schmelzeisen & Frolich, 1993 Level II).…”
Section: Chaptermentioning
confidence: 98%
“…9 Dexamethasone is a potent corticosteroid with analgesic, anti-inflammatory and antiemetic action. [10][11][12] Preoperative dexamethasone has been reported to reduce the incidence of postoperative pain and swelling following oral surgeries. [10][11][12] A previous study undertaken to evaluate the effect of dexamethasone on postoperative sore throat after endotracheal intubation did not address the numerous confounding factors responsible for sore throat.…”
mentioning
confidence: 99%
“…[10][11][12] Preoperative dexamethasone has been reported to reduce the incidence of postoperative pain and swelling following oral surgeries. [10][11][12] A previous study undertaken to evaluate the effect of dexamethasone on postoperative sore throat after endotracheal intubation did not address the numerous confounding factors responsible for sore throat. 13 With this background knowledge, a prospective, randomized, double-blind, placebo-controlled study was undertaken to test whether a reduction in the incidence and severity of postoperative sore throat could be achieved by preoperative administration of intravenous dexamethasone in patients receiving general anesthesia with endotracheal intubation.…”
mentioning
confidence: 99%